Identification of Economic Characters and Agro-biological Characters of Cotton at Various Growth Stages - Sh.U. Rakhmonov; G.Q. Diyarov; Z.T. Bolqiyev (American Journal of Botany and Bioengineering, 2026)
A feature of the progressive development of this article is an assessment of major economic traits of cotton and agobiological properties of cotton during the developmental process. An assessment of various cotton phenotypes in respect to productivity potential, stress tolerance, and biotic and abiotic features. These results provide a scientific foundation to improve cotton cultivation efficiency and appropriate variety selection and agronomy management.